The year in tech, 2021 : the insights you need from Harvard Business Review. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2021)
"A year of HBR's essential thinking on tech--all in one place. From the latest applications of AI to blockchain-enabled business models to 5G networks, the most important technological innovations of the past year are reshaping the present and future of business. What should you and your company be doing now to take advantage of the new opportunities they are creating? The Year in Tech, 2021: The Insights You Need from Harvard Business Review will help you understand today's most essential thinking on these topics, what the latest tech innovations mean for your organization, and how you can use them to compete and win in the new landscape of business."--
Section 1. New tech and the evolving consumer experience: How voice assistants could change the way we shop / by Kane Simms -- Four questions retailers need to ask about augmented reality / by Darrell K. Rigby, Mikey Vu, and Asit Goel -- Section 2. Working better with advanced technologies: Building ethical AI for talent management / by Tomas Chamorro-Premuzic, Frida Polli, and Ben Dattner -- The 5 kinds of blockchain projects (and which to watch out for): starting one because of FOMO is never a good idea / by David Furlonger and Christophe Uzureau -- Learning to work with intelligent machines: tech is moving trainees away from learning opportunities and experts away from the action / by Matt Beane -- Section 3. The next tech trends in business: 5G's potential, and why businesses should start preparing for it / by Omar Abbosh and Larry Downes -- It's not just faster internet: can biometrics predict a viral marketing campaign? / by Jacob L.H. Jones, Matthew Gillespie, Kelsey Libert -- Neurometrics help us get a clearer view into the minds of consumers: how wearable AI will amplify human intelligence / by Laura Golembiewski -- The era of antisocial social media / by Sara Wilson -- Section 4. Big tech, big problems: Why it's so hard for users to control their data / by Bhaskar Chakravorti -- How to safeguard against cyberattacks on utilities / by Stuart Madnick -- A survival guide for startups in the era of tech giants / by Thales S. Teixeira.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Business -- Technological innovations; Industrial management; Success in business; elektronické knihy; electronic books